2021
DOI: 10.3390/jcm10061157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperbaric Oxygen Therapy in Children with Severe Atopic Dermatitis

Abstract: In the course of atopic dermatitis (AD), the overactivity of the immune system, associated with predominant Th2 lymphocyte responses, is observed, which leads to an increased inflammatory reaction. Cases of a severe course of atopic dermatitis lead to the search for new therapeutic options. The aim of this study was to assess the effects of hyperbaric oxygen therapy (HBOT) treatment for severe cases of AD in children. A total of 15 children with severe AD underwent therapy. The influence of HBOT on the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…HBOT is known to promote wound healing via angiogenesis, collagen/fibroblast synthesis, and antimicrobial activity 54,55 . HBOT has been used successfully and safely to treat children with severe atopic dermatitis 56 . A RCT of 43 adult patients with HS reported that subjects who were treated with adjunct HBOT had an improved response to oral clindamycin and rifampin compared to those who only received antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBOT is known to promote wound healing via angiogenesis, collagen/fibroblast synthesis, and antimicrobial activity 54,55 . HBOT has been used successfully and safely to treat children with severe atopic dermatitis 56 . A RCT of 43 adult patients with HS reported that subjects who were treated with adjunct HBOT had an improved response to oral clindamycin and rifampin compared to those who only received antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 HBOT has been used successfully and safely to treat children with severe atopic dermatitis. 56 A RCT of 43 adult patients with HS reported that subjects who were treated with adjunct HBOT had an improved response to oral clindamycin and rifampin compared to those who only received antibiotic therapy. Further investigations are needed to characterize this potential synergistic benefit in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%